A review of the submerged prehistory and palaeolandscapes of the British Isles. Issue 6 (December 2015) - Bicket, Andrew; Tizzard, Louise
Abstract: Significant progress has been made on the investigation of Quaternary submerged prehistory in the British Isles. Mainly through collaboration with industry, a considerable knowledge base has been developed on the distribution and nature of preserved palaeolandscapes of the last 1 million years in UK waters. A diverse array of material has been recovered from the seabed including bone and stone artefacts, extinct fauna, peat deposits, submerged forests and other remnants of relict landscapes from around the British Isles. Archaeological sites are rarer but Palaeolithic and Mesolithic examples are providing critical resources to reinterpret early prehistory in association with Quaternary palaeogeography.